Photon beam line of the water window FEL for the EuPRAXIA@SPARC_LAB project. (July 2020) - Villa, F; Balerna, A; Chiadroni, E; Cianchi, A; Coreno, M; Dabagov, S A; Cicco, Di; Gunnella, R; Marcelli, A; Masciovecchio, C; Minicucci, M; Morante, S; et al.
Abstract: A proposal for building a new Free Electron Laser facility at the Laboratori Nazionali di Frascati, EuPRAXIA@SPARC_LAB, is at present under consideration. This FEL facility will exploit plasma acceleration to produce ultra-bright photon pulses with durations of few femtoseconds down to the wavelengths between 2 and 4 nm, in the so called "water window". The main class of experiments to be performed will include coherent diffraction imaging, soft X-ray absorption spectroscopy, Raman and photofragmentation measurements. In this article we present the updates on the photon beamlines design for the facility.